Antecedents and Consequences of Attitude toward Femvertising - Namhyun Um(엄남현) (한국콘텐츠학회 논문지, 21(1), 2021)
As femvertising has raised a great deal of attentions in Korea and abroad, femvertising which focuses on women’s equality and empowerment has also brought much pubic attentions. Despite of much attentions, research on femvertising has been scarce. Thus, this study is designed to examine antecedents and consequences of attitude toward femvertising. For antecedents, this study proposes perceived congruence and perceived authenticity; as consequences, it proposes attitude toward brand, purchase intention, and e-word-of-mouth intention. A total of 278 college students participated in the study in return for course credits. Study results suggest that both perceived congruence and perceived authenticity are positively related to attitude toward advertising. In sum, when consumers perceive that femvertising messages are congruent with the company’s brand image and the ad messages are authentic, positive attitude toward ads is likely to increase. Findings also suggest that attitude toward femvertising is positively related to attitude toward brand, purchase intention, and e-word-of-mouth-intention. In the last section of this paper, we discuss theoretical and practical implications.. KCI Citation Count: 0